Thirteen doorways, wolves behind them all - Ruby, Laura (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2019)
Abandoned in a Chicago orphanage with her sister, Frankie endures injustice, poverty, and violence while struggling to survive in the years leading up to World War II.
Keywords: Sisters -- Fiction; Orphanages -- Fiction; Depressions -- 1929 -- Fiction; Historical fiction